Active Usage of ICT in Jewellery Art Design Courses - Coşkun, Metin; Coşkun Karabulut, Burcu (Procedia Information Technology & Computer Science, 2012)
The aim of this study is to determine the effects of Information and Communication Technologies usage in the area of jewellery design which is the rising sort of arts. The research is a qualitative research. By using “content analysis” methods, datas from scientific studies will be examined and results will be shared. It is thought that the study will be useful for illuminating the usage of information technologies in jewellery arts design area.
Keywords: Jewellery Design, Digital Jewellery, Information and Communication Technologies